Patient-reported outcomes with initiation of fluticasone furoate/vilanterol versus continuing usual care in the Asthma Salford Lung Study. (August 2018) - Svedsater, Henrik; Jones, Rupert; Bosanquet, Nick; Jacques, Loretta; Lay-Flurrie, James; Leather, David A.; Vestbo, Jørgen; Collier, Susan; Woodcock, Ashley
Abstract: Background: The Asthma Salford Lung Study demonstrated the effectiveness and safety of initiating once-daily inhaled fluticasone furoate/vilanterol (FF/VI) versus continuing usual care (UC) in asthma patients in UK primary care [1]. Here, we report a detailed analysis of patient-reported outcome (PRO) endpoints. Methods: Adults with symptomatic asthma maintained on inhaled corticosteroids (ICS) ± long-acting beta2 -agonists (LABA) were randomized 1:1 to initiate FF/VI (100 [200]/25 μg) or continue UC. PROs were measured using the Asthma Control Test (ACT), Standardized Asthma Quality of Life Questionnaire (AQLQ [S]), Work Productivity and Activity Impairment: asthma questionnaire, and EQ-5D-3L (EuroQol 5-Dimensions 3-Levels) questionnaire, at timepoints across the 12-month study period. Results: The individual components of ACT response (total score ≥20 or improvement from baseline ≥3) both contributed to the composite primary effectiveness endpoint at Week 24, with odds ratios favoring FF/VI over UC in both cases. Patients initiating FF/VI versus continuing UC were more likely to maintain/improve asthma control, regardless of baseline control status. The odds of patients being responders on AQLQ (S) total score and on individual AQLQ domains at Week 52 were significantly higher for FF/VI versus UC (all p  < .001). FF/VI was associated with significantly greater reductions in overall work and activity impairment due to asthma (both p  < .001), and a significantly greater change from baseline in EQ visual analogue scale score ( p  = .007), versus UC at Week 52. PRO findings were consistent across baseline ICS and ICS/LABA subsets. Conclusions: Initiation of FF/VI versus continuing UC was associated with consistent improvements in PROs. Graphical abstract: Highlights: Initiating FF/VI consistently improved asthma PROs vs continuing UC. Consistent benefit of FF/VI vs UC on asthma control regardless of initial control. Benefit at Wk 52 for FF/VI vs UC on total AQLQ and individual AQLQ domain scores. Greater reduction in overall work and activity impairment at Wk 52 for FF/VI vs UC. Consistent benefits of FF/VI demonstrated across all patient subsets analyzed.